Psikologi Peluang Kewirausahaan: Proses Kognitif Pengusaha Startup Digital dalam Opportunity Recognition - Sadida Fatin Aruni; Rahmat Hidayat (Jurnal Psikologi, 2019)
Developed countries have at least 2% of entrepreneurs from the total population of the country. However, Indonesia has a very low number of entrepreneurs as well as an increasing unemployment rate over the years. Recently, the development of entrepreneurship in Indonesia dominated by the growing number of digital startup. Moreover, Indonesia is a country with the largest number of a digital startup in Southeast Asia. Initial psychological studies on entrepreneurship are focused on the personal characteristics of the entrepreneurs. However, conclusions from more than 30 years of research indicate that there are no special personality characteristics of entrepreneurs and non-entrepreneurs. In essence, the heart of entrepreneurship lies in the ability to recognize an opportunity. Opportunity recognition is a mechanism that happens in an individual’s cognitive process. Therefore, this study intended to reveal the cognitive processes that take place when entrepreneurs, in particular, the founders of digital startups, in the identification of entrepreneurial opportunities. This research uses the think-aloud protocol method with protocol analysis. Based on this research, we found that in the process of opportunity recognition, entrepreneurs focus their cognitive efforts on the market (demand) and technology (supply) as well as build relationships and meaningful patterns in these two aspects through structural relationship processing. This study provides an in-depth description of the cognitive processes that occur when entrepreneurs recognize entrepreneurial opportunities through structural alignment processes.